2017
DOI: 10.1155/2017/2510695
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Extracorporeal Membrane Oxygenation Support for Children with Acute Myocarditis

Abstract: The clinical presentation of acute myocarditis in children may range from asymptomatic to sudden cardiac arrest. This study analyzed the clinical spectrum of acute myocarditis in children to identify factors that could aid primary care physicians to predict the need for extracorporeal membrane oxygenation (ECMO) earlier and consult the pediatric cardiologist promptly. Between October 2011 and September 2016, we retrospectively analyzed 60 patients aged 18 years or younger who were admitted to our pediatric eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
(33 reference statements)
3
22
0
1
Order By: Relevance
“…A previous study reported that ECMO was initiated in approximately 17% of the children who were hospitalized with myocarditis. 17) Another study in US that used the Pediatric Health Information System database reported that ECMO was initiated in 18.9% of children hospitalized with myocarditis. 6) The rate of ECMO use in our study was slightly lower than that in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that ECMO was initiated in approximately 17% of the children who were hospitalized with myocarditis. 17) Another study in US that used the Pediatric Health Information System database reported that ECMO was initiated in 18.9% of children hospitalized with myocarditis. 6) The rate of ECMO use in our study was slightly lower than that in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…ECMO was used in 16.7% and 7.4% of children in Taiwan and US, respectively, due to acute myocarditis. 13 , 14 According to the previous studies, 15 17 the following were indications for the ECMO therapy: 1) low blood pressure (systolic blood pressure <60 mmHg for children, and <50 mmHg for infants) despite an inotropic equivalent (IE, mg/kg/min = dopamine + dobutamine +15× milrinone +100 * epinephrine +100 * norepinephrine +100 * isoproterenol), >40 mg/kg/min support, 2) cardiac and pulmonary failure refractory to medical therapy, 3) cardiac arrest requiring continuous CPR, and 4) uncontrolled arrhythmia including VT and ventricular fibrillation. We conclude that children with FM requiring continuous CPR should definitely be considered for ECMO support, just as the case reported above.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that poor left ventricular systolic function and in-hospital arrhythmia were associated with poor short-term outcomes [ 8 , 9 ]. In children with AFM, initial serum troponin-I cutoff values greater than 14.21 ng/mL may also indicate the need for extracorporeal membrane oxygenation (ECMO) support [ 10 ]. However, most studies have focused on pediatric patients with AFM, and we hypothesized that the predictors of clinical outcomes would be similar in adult patients.…”
Section: Introductionmentioning
confidence: 99%